Sistem Penjualan LPG Berbasis Web Dengan Menggunakan E-KTP: Studi Kasus : BUM Desa Podho Joyo Sukorejo - Moh. Rizal Bashori; Putri Aisyiyah Rakhma Devi (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Web-based LPG gas sales system using E-KTP is an application designed to facilitate the process of selling LPG gas online by using E-KTP as a user identity verification tool. This system was built with the aim of increasing efficiency and security in the LPG gas sales transaction process. This system utilizes web technology to allow users to sell LPG gas online through a platform accessed through a web browser. Users will be required to upload a photo of their E-KTP as part of the identity verification process. After identity verification, users can place an order for LPG gas according to their needs. The system is also equipped with an LPG gas stock management feature, so that sellers can monitor their LPG gas stock in real-time and procure new LPG gas if the stock is running low. In addition, the system is also equipped with an LPG gas delivery tracking feature, so that users can track the status of their LPG gas shipments from the warehouse to the delivery location. With this web-based LPG gas sales system using E-KTP, it is expected to increase efficiency in the LPG gas sales process, as well as increase security in online transactions by using E-KTP as a means of verifying user identity.